Insights into Childhood Malnutrition: An Analysis on Food Vulnerability and Stunting using 2021 Indonesian Nutritional Status Survey Data - Sanggelorang, Yulianty; Sebayang, F. Ari Anggraini; Malonda, Nancy S H; Rumayar, Adisti A (Media Gizi Indonesia, 2024)
Stunting, a consequence of childhood malnutrition, stems from various factors, including unaddressed food vulnerability during the critical early stages of life, from conception to 24 months. Early loss of developmental opportunities, particularly that in relation to height, leads to an irreversible inability to achieve optimal growth. This study aimed to analyze the relationship between food vulnerability and stunting among children aged 0-59 months in the East Bolaang Mongondow Regency. The research utilized secondary data from the 2021 Indonesian Nutritional Status Survey (INSS), encompassing all selected households with children under five within the census blocks. After applying appropriate weighting procedures, the sample size was 8,893. The study included anthropometric measurements (body height/length) and assessments of various indicators of household food vulnerability (the inability of an individual or a group of individuals to obtain sufficient and appropriate food for a healthy and active life). The findings revealed significant correlations (p-value < 0.05) between food vulnerability status and stunting. Children from the food-vulnerable group had a 4.661 times higher risk of experiencing stunting compared to those from the food-secure group. This study concludes that food vulnerability is a significant risk factor in the development of stunting in children under five in Indonesia. Furthermore, factors associated with vulnerability such as limited access to nutritious food and food variety could contribute to hindering child growth.  These findings have important implications for the development of nutritional policies and interventions in Indonesia.